Is duodenal biopsy always necessary for the diagnosis of coeliac disease in adult patients with high anti-tissue transglutaminase (TTG) antibody titres?. Issue 4 (25th June 2021) - Beig, Junaid; Rostami, Kamran; Hayman, David T S; Hassan, Summer; Gerred, Stephen; Ogra, Ravinder
Abstract : Objective: Avoiding duodenal biopsy in adults for coeliac disease (CD) diagnosis is controversial. Some retrospective and prospective studies have shown that CD can be reliably diagnosed in adults with serology rather than duodenal biopsies. This study aimed to check the accuracy of a cut-off value of ≥10 upper limit of normal of anti-tissue transglutaminase antibody (anti-TTG IgA) titres for CD diagnosis in adult patients. Method: We retrospectively analysed adult patients (≥16 years) who underwent gastroscopy from 2013 to 2018 for positive coeliac serology. The relationship between titres and disease was determined by using linear models, whereas sensitivity and specificity were assessed by receiver operator curve. Results: We analysed 144 newly anti-TTG antibody-positive adult patients with a median age of 48.5 years (IQR 32–62); among them, 86 (60%) patients had CD (Marsh III: n=68 and Marsh II and I: n=18) with a higher prevalence in females (n=59 (69%)) and Europeans (n=60 (70%)). Fifty (58%) patients with CD had colonoscopy and five (6%) had imaging; only six patients were diagnosed with additional conditions. An anti-TTG IgA titre cut-off value of 150 U/L was 100% specific for CD in our dataset, with 70% (95% CI: 60% to 88%) sensitivity for this patient group. Conclusion: Coeliac serology using anti-TTG IgA with titres ≥10× normal value is an excellent predictor of CD, irrespective of age, gender and ethnicity. Duodenal biopsy may not be necessary in selected adult patients with CD, especially younger than 50 years of age without additional gastrointestinal red-flag signs and symptoms.